2017
DOI: 10.1111/idh.12283
|View full text |Cite
|
Sign up to set email alerts
|

Plaque removal with triple‐headed vs single‐headed manual toothbrushesa systematic review

Abstract: From this review emerges the recommendation that the use of a triple-headed manual toothbrush instead of a single-headed manual toothbrush might be favorable with respect to plaque removal in case a care-dependent individual is brushed by a caregiver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 26 publications
3
27
0
2
Order By: Relevance
“…27 Good plaque control is crucial to maintain periodontal health, and data related to tooth brushing behavior supported this statement. 28,29,30 An 11-year study showed that tooth brushing was associated with a decrease in the number of teeth with periodontal pocketing. There was a clear dose-response relationship between tooth brushing frequency and change in the number of teeth with PPD ≥ 4 mm.…”
Section: Periodontal Treatmentmentioning
confidence: 99%
“…27 Good plaque control is crucial to maintain periodontal health, and data related to tooth brushing behavior supported this statement. 28,29,30 An 11-year study showed that tooth brushing was associated with a decrease in the number of teeth with periodontal pocketing. There was a clear dose-response relationship between tooth brushing frequency and change in the number of teeth with PPD ≥ 4 mm.…”
Section: Periodontal Treatmentmentioning
confidence: 99%
“…5,[7][8][9][17][18][19][20]30,31 This could be due to that the brush includes sonic movement and three-surface cleaning that improves plaque removal and thus reduce bleeding on probing. [7][8][9][17][18][19][20]30,31 This is in agreement with previous reports on the superior efficacy of sonic brushes in plaque removal. [7][8][9]30,31 Also, this could be due to improved compliance with brushing and oral hygiene as the toothbrush is working on all tooth surfaces simultaneously.…”
Section: Ta B L E 3 (Continued)mentioning
confidence: 99%
“…Outro estudo evidenciou a superioridade da escova elétrica na remoção da placa e diminuição da gengivite a curto e a longo prazo, quando comparada com a escova manual 20 . Em um estudo realizado com escova de cabeça tripla, ficou demonstrado sua superioridade no controle do biofilme dentário em superfícies lisas de dentes posteriores, quando comparada com a convencional 24 tendo sido considerada a mais indicada para pacientes que necessitam de cuidadores 25 . Ensaios clínicos sobre eficácia de escovas manuais concluíram, que não existe superioridade entre os modelos de dispositivos manuais [26][27][28] .…”
Section: Discussionunclassified